A fault‐tolerant group key agreement protocol exploiting dynamic setting. (21st January 2013) - Cheng, Zi‐Yao; Liu, Yun; Chang, Chin‐Chen; Guo, Cheng
SUMMARY A fault‐tolerant group key agreement is an essential infrastructure for Internet communication among all involved participants; it can establish a secure session key no matter how many malicious participants exit simultaneously in an effort to disrupt the key agreement process. Recently, Zhao et al. proposed an efficient fault‐tolerant group key agreement protocol named efficient group key agreement that can resist denial‐of‐service attacks, reply attacks, man‐in‐middle attacks, and common modulus attacks; it can also preserve forward secrecy with lower computational cost than previous protocols. We show that it is still vulnerable to active attacks by malicious participants and modify the corresponding security weakness adaptively. Furthermore, we propose an efficient fault‐tolerant group key agreement based on a binary tree structure and enhance it to a dynamic setting where participants can leave or join the group arbitrarily according to their preferences with instant session key refreshment. Additionally, our session key refreshment is based on secure key updating to protect forward/backward confidentiality and is resistant to active/passive attacks. The performance analysis shows that our proposed protocol has lower computational cost and little additional communication cost exploiting dynamic setting. Copyright © 2013 John Wiley & Sons, Ltd.